Special cementing material for low-shrinkage high-airtightness concrete and preparation method of special cementing material

By using low-thermal silicate cement clinker and other modified components in the gelling materials, the microstructure and pore size distribution of the gelling materials are optimized, and the problem of insufficient airtightness and durability of existing gelling materials in complex environments is solved, and gelling materials with low shrinkage, high airtightness and excellent mechanical properties are achieved.

CN119797862AActive Publication Date: 2025-04-11JIAHUA SPECIAL CEMENT
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510003278.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

Existing gelling materials are difficult to meet the needs of high airtightness and durability in complex environments, and the shrinkage and gas permeability resistance of conventional silicate-based gelling materials are insufficient.

Method used

The low-temperature silicate cement clinker is used as the main method, combined with sulfur-aluminate cement clinker, lightly calcined magnesium oxide and diethanol monoisopropanolamine, the pore size distribution and microstructure are optimized through the micro-expansion effect and the activated iron phase hydration reaction, and sub-micrometer-scale silica fume, fly ash, glass powder and predispersed carbon nanotubes are further added to improve the airtightness and mechanical properties of the cemented material.

Benefits of technology

It achieves low shrinkage, high airtightness and excellent mechanical properties, is suitable for complex engineering environments, and significantly improves the compressive strength and airtightness of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226082080000021
    Figure BDA0005226082080000021
  • Figure BDA0005226082080000111
    Figure BDA0005226082080000111
  • Figure BDA0005226082080000121
    Figure BDA0005226082080000121
Patent Text Reader

Abstract

The invention discloses a special cementing material for low-shrinkage high-airtightness concrete and a preparation method thereof, and the special cementing material comprises the following components in percentage by mass: 48-63 wt% of low-heat Portland cement clinker, 6-14 wt% of sulphoaluminate cement clinker, 3-5 wt% of light calcined magnesia, 7-10 wt% of submicron silica fume, 9-18 wt% of fly ash and 6-12 wt% of glass powder. The gypsum accounts for 2-3 wt% of the total mass of the raw materials, the diethanolisopropanolamine accounts for 0.03 wt% of the total mass of the raw materials, and the pre-dispersed carbon nanotubes account for 0.1 wt% of the total mass of the raw materials. The special cementing material disclosed by the invention is reasonable in particle size distribution, and the components generate an interactive superposition effect, complement and promote each other, so that the hydrated cementing material is continuously compact, and the airtight concrete prepared from the cementing material can keep excellent airtight performance and volume stability in each stage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a special cementitious material for low-shrinkage and high-air-tightness concrete and a preparation method thereof. Background Art

[0002] As the most widely used building material, the durability of concrete has always been one of the research focuses in the field of concrete materials science and technology. Concrete durability can not only well reflect the safety, reliability and service life of concrete structures under various environmental conditions, but also its evaluation and enhancement can ensure the stability and sustainability of concrete in various application scenarios.

[0003] The durability process of concrete materials is relatively complex, but it is basically related to the pore structure of concrete and the material transfer in the pore structure, so the durability of concrete mainly depends on permeability. Gas permeability is a direct physical representation of the ability of gas media to migrate in cement-based porous materials under pressure. It is an ideal physical parameter to measure the durability and density of concrete materials. As a durability performance indicator, it has been widely used in many engineering structures in the field of building materials, such as tunnel lining structures containing gas, vacuum pipelines, concrete containment in nuclear power projects, radiation-resistant concrete, reinforced concrete structures, and other buildings that require high airtightness. Research scholars have also conducted relevant research on the air tightness of concrete. Patent document CN114573288A discloses a high-air-tightness concrete. By adding characteristic components and pre-treated highly absorbent resins to the concrete components, the concrete composition and microscopic pore structure are optimized, so that high air tightness and stability can be maintained in a long-term low-vacuum environment; Patent document CN114133190A discloses an airtight concrete. By using machine-made sand with a suitable ratio, an airtight agent and an expansion agent, the air tightness and impermeability of the concrete are increased to meet the requirements of tunnel construction; Patent document CN110698137A improves the concrete microstructure and introduces stable elastic bubbles by adding mineral admixtures and special air-entraining agents, thereby improving the ability to resist gas penetration and pressurized water penetration.

[0004] The above-mentioned technical means for preparing airtight concrete mainly improve the airtightness of concrete by adding characteristic components, mineral admixtures, internal curing materials, controlling the quality of concrete materials, optimizing the concrete mix ratio, etc. However, the most important cementitious materials all use ordinary silicate-based cementitious materials without any changes. However, with the development of modernization and the needs of engineering construction in special fields, more stringent construction and service environments, higher functions and gas permeability resistance requirements have posed new challenges to airtight concrete. As the main component of concrete, cementitious materials have a good improvement effect on the pore structure due to their hydration products, can provide strong structural support, promote the durability of concrete and realize the diversity of design structures, and are often used. Conventional ordinary silicate-based cementitious materials lack engineering application targeting, cannot meet the complex and changeable service environment, have poor durability and short service life. Therefore, it is urgent to design a special cementitious material for low-shrinkage and high-airtight concrete from the perspectives of cementitious material composition, structure and performance, so as to improve the airtightness of concrete and adapt to more complex engineering environments. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a low-shrinkage and high-airtightness concrete special cementitious material and a preparation method thereof.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] In one aspect, the present invention provides a low-shrinkage, high-air-tightness concrete-specific cementitious material, comprising the following raw materials by mass percentage:

[0008]

[0009] The invention also comprises 2-3wt% of gypsum, 0.03wt% of diethanol monoisopropanolamine and 0.1wt% of pre-dispersed carbon nanotubes in terms of the total mass percentage of the above raw materials.

[0010] Furthermore, the mineral composition of the low-heat Portland cement clinker includes: 29.9wt% C3S, 46.3wt% C2S, 1.8wt% C3A and 15.3wt% C4AF; the specific surface area of ​​the low-heat Portland cement clinker is 350-370m 2 / kg, 3d compressive strength ≥14MPa.

[0011] Furthermore, the mineral composition of the sulphoaluminate cement clinker includes: 27.5wt% C2S, 5.3wt% C4AF; the specific surface area of ​​the sulphoaluminate cement clinker is 390-420m 2 / kg, 3d compressive strength ≥40MPa.

[0012] Furthermore, the light-burned magnesium oxide has a magnesium oxide content of ≥85wt%, an active magnesium oxide content of ≥65wt%, and a particle size of ≤40μm.

[0013] Furthermore, the SiO2 content in the submicron silica ash is greater than 93wt%, and the specific surface area is 23000m 2 / kg, 7d activity index ≥105%.

[0014] Furthermore, the fly ash is Class I fly ash with a specific surface area of ​​398m 2 / kg; the glass powder is waste quartz glass powder with a specific surface area of ​​450m 2 / kg.

[0015] Furthermore, the gypsum is natural gypsum or mixed gypsum, the anhydrite content in the natural gypsum or mixed gypsum is not more than 50wt% of the total gypsum, and the specific surface area of ​​the gypsum is 317-421m 2 / kg; the solid content of the diethanol monoisopropanolamine is ≥85wt%, and the pH value is 10.24.

[0016] Furthermore, the pre-dispersed carbon nanotubes are obtained by pre-dispersing carbon nanotubes with a length of 100 to 200 μm and a diameter of 7 to 9 nm.

[0017] Furthermore, the preparation of the pre-dispersed carbon nanotubes is as follows: (1) weighing carbon nanotubes, polyvinyl pyrrolidone dispersant and deionized water in a mass ratio of 0.1:0.3:100 for later use; (2) adding the carbon nanotubes and polyvinyl pyrrolidone dispersant into deionized water, stirring, sealing and ultrasonically treating, and then high-pressure homogenizing to obtain a pre-dispersed liquid; (3) freeze-drying the pre-dispersed liquid to remove all water, and then placing it in a high-temperature drying oven to remove the polyvinyl pyrrolidone dispersant to obtain pre-dispersed carbon nanotubes;

[0018] Preferably, the ultrasonic treatment in (2) is repeated 6 times, and each ultrasonic treatment lasts for 5 minutes;

[0019] Preferably, the temperature of the high temperature drying oven (3) is 600° C., and the treatment time is 3 h.

[0020] On the other hand, the present invention provides a method for preparing a low-shrinkage and high-airtightness concrete special cementitious material, comprising the following steps:

[0021] S1. Weigh low-heat silicate cement clinker, sulphoaluminate cement clinker, light-burned magnesia, submicron silica fume, fly ash and glass powder according to the mass percentage and set aside; weigh gypsum, diethanol monoisopropanolamine and pre-dispersed carbon nanotubes according to the percentage of the total mass of the above raw materials and set aside;

[0022] S2, take out the reserved pre-dispersed carbon nanotubes, and weigh 10 times the mass of low-heat silicate cement clinker and 81.6 times the mass of isopropanol of the pre-dispersed carbon nanotubes, wherein the low-heat silicate cement clinker is weighed from the corresponding raw materials reserved in S1; divide the isopropanol into two parts, add the pre-dispersed carbon nanotubes to one part of the isopropanol, stir to dissolve and ultrasonically disperse to obtain a first mixture, then add the low-heat silicate cement clinker and the other part of the isopropanol to the first mixture, stir to dissolve and ultrasonically disperse to obtain a second mixture; place the second mixture in a high-temperature drying oven for treatment to remove the isopropanol, and obtain a clinker-CNT dry powder;

[0023] Preferably, when the pre-dispersed carbon nanotubes are added to a portion of isopropanol, stirred to dissolve and ultrasonically dispersed, the ultrasonic time is 30 minutes;

[0024] Preferably, when adding the low-heat Portland cement clinker and another portion of isopropanol to the first mixture, stirring to dissolve and ultrasonically dispersing, the ultrasonic time is 90 minutes;

[0025] Preferably, the temperature of the high temperature drying oven is 100±5°C and the treatment time is 24h;

[0026] S3, the sulphoaluminate cement clinker reserved in S1, light-burned magnesia, submicron silica fume, fly ash, glass powder, gypsum, diethanol monoisopropanolamine and the remaining low-heat silicate cement clinker, and the clinker-CNT dry powder obtained in S2 are mixed evenly to obtain the special cementitious material for low shrinkage and high airtightness concrete.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The special cementitious material of the present invention is mainly composed of low-heat silicate cement clinker with low water demand, low hydration heat, high durability and excellent long-term mechanical properties. It is modified by introducing appropriate amounts of sulphoaluminate cement clinker, light-burned magnesia and diethanol monoisopropanolamine (DEIPA). The micro-expansion effect of sulphoaluminate cement clinker and light-burned magnesia is used to effectively compensate for the shrinkage of low-heat silicate cement clinker, so that the special cementitious material system has a lower hydration volume shrinkage; and DEIPA is used to modify Fe in the system. 3+ The complexation of gypsum effectively activates the high content of (C4AF) iron phase in low-heat Portland cement clinker. Under the synergistic effect with gypsum, it can further enhance the hydration reaction of the ferrite phase in the slurry, accelerate the consumption of DEIPA and the formation of ettringite (AFt) and monosulfoaluminate (AFm) in the hydration products, promote the dissolution of mineral admixtures, optimize the pore size distribution, densify the microstructure, and effectively improve the early mechanical properties. At the same time, by adding a specific proportion of fly ash and glass powder, the lubricity and dispersibility of the special cementitious material are improved, and the overall later strength is improved.

[0029] 2. The present invention controls the particle size of each material, wherein submicron silica fume and pre-dispersed carbon nanotubes are used as fine powders, which can be filled into the pores of other materials to improve the density of the matrix. At the same time, the carbon nanotubes are pre-dispersed, which can effectively reduce the degree of entanglement between the carbon nanotubes without damaging the structure of the carbon nanotubes, making their network structure loose, and disperse them in the low-heat silicate cement clinker particles, which is conducive to achieving uniform dispersion of carbon nanotubes in cementitious materials, can effectively fill the micropores generated after cement hydration, and play a good bridging and filling role in the internal pores, enhance the density of the matrix, and effectively inhibit the development of microcracks, thereby significantly improving the mechanical properties of concrete, and improving the shrinkage resistance and airtightness of concrete.

[0030] 3. The particle size distribution of the special cementitious material of the present invention is reasonable, and the components produce an interactive superposition effect, complement each other, and promote each other, so that the hydrated cementitious material is continuously dense, and the prepared airtight concrete can maintain excellent airtight performance and volume stability at all stages. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0032] In the embodiment of the present invention, the mineral composition of the low heat Portland cement clinker includes: 29.9wt% C3S, 46.3wt% C2S, 1.8wt% C3A and 15.3wt% C4AF; the specific surface area of ​​the low heat Portland cement clinker is 350-370m 2 / kg, 3d compressive strength ≥14MPa.

[0033] In the embodiment of the present invention, the mineral composition of sulphoaluminate cement clinker includes: 27.5wt% C2S, 5.3wt% C4AF; the specific surface area of ​​the sulphoaluminate cement clinker is 390-420m 2 / kg, 3d compressive strength ≥40MPa.

[0034] In the embodiment of the present invention, the light-burned magnesium oxide has a magnesium oxide content of ≥85wt%, an active magnesium oxide content of ≥65wt%, and a particle size of ≤40μm.

[0035] In the embodiment of the present invention, the SiO2 content in the submicron silica ash is greater than 93wt%, and the specific surface area is 23000m 2 / kg, 7d activity index ≥105%.

[0036] In the embodiment of the present invention, the fly ash is Class I fly ash with a specific surface area of ​​398m 2 / kg.

[0037] In the embodiment of the present invention, the glass powder is waste quartz glass powder with a specific surface area of ​​450m 2 / kg.

[0038] In the embodiment of the present invention, the gypsum is natural gypsum or mixed gypsum, the anhydrite content in the natural gypsum or mixed gypsum is not more than 50wt% of the total gypsum, and the specific surface area of ​​the gypsum is 317-421m 2 / kg; the solid content of the diethanol monoisopropanolamine is ≥85wt%, and the pH value is 10.24.

[0039] In the embodiment of the present invention, the pre-dispersed carbon nanotubes are carbon nanotubes with a length of 100 to 200 μm and a diameter of 7 to 9 nm obtained by pre-dispersing.

[0040] The preparation of pre-dispersed carbon nanotubes is as follows: (1) weighing carbon nanotubes, polyvinyl pyrrolidone dispersant and deionized water in a mass ratio of 0.1:0.3:100 for later use; (2) adding carbon nanotubes and polyvinyl pyrrolidone dispersant to deionized water, stirring with a glass rod, sealing, placing in an ultrasonic disperser for ultrasonic treatment, ultrasonication for 5 minutes in each stage, repeating the ultrasonication operation 6 times, and accumulating ultrasonication time for 30 minutes, and then placing in a high-pressure homogenizer for high-pressure homogenization to obtain a pre-dispersed liquid; (3) freeze-drying the pre-dispersed liquid to remove all water, and then placing in a 600°C high-temperature drying oven for treatment for 3 hours to remove the polyvinyl pyrrolidone dispersant to obtain pre-dispersed carbon nanotubes;

[0041] In an embodiment of the present invention, a method for preparing a low-shrinkage and high-air-tightness concrete-specific cementitious material comprises the following steps:

[0042] S1. Weigh low-heat silicate cement clinker, sulphoaluminate cement clinker, light-burned magnesia, submicron silica fume, fly ash and glass powder according to the mass percentage and set aside; weigh gypsum, diethanol monoisopropanolamine and pre-dispersed carbon nanotubes according to the percentage of the total mass of the above raw materials and set aside;

[0043] S2, take out the reserved pre-dispersed carbon nanotubes, and weigh 10 times the mass of low-heat silicate cement clinker and 81.6 times the mass of isopropanol of the pre-dispersed carbon nanotubes, wherein the low-heat silicate cement clinker is weighed from the corresponding raw materials reserved in S1; divide the isopropanol into two parts, add the pre-dispersed carbon nanotubes to one part of the isopropanol, stir to dissolve, and ultrasonically disperse for 30 minutes to obtain a first mixture, then add the low-heat silicate cement clinker and the other part of the isopropanol to the first mixture, stir to dissolve, and ultrasonically disperse for 90 minutes to obtain a second mixture; place the second mixture in a high-temperature drying oven at 100±5°C for 24 hours to remove the isopropanol, and obtain a clinker-CNT dry powder;

[0044] S3, the sulphoaluminate cement clinker reserved in S1, light-burned magnesia, submicron silica fume, fly ash, glass powder, gypsum, diethanol monoisopropanolamine and the remaining low-heat silicate cement clinker, and the clinker-CNT dry powder obtained in S2 are mixed evenly to obtain a special cementitious material for low-shrinkage and high-air-tightness concrete.

[0045] Example 1

[0046] As a preferred embodiment of the present invention, the specific composition of the low shrinkage and high airtightness concrete special cementitious material disclosed in this embodiment is shown in Table 1 below.

[0047] Table 1

[0048] raw material Mass percentage (wt%) Low heat Portland cement clinker 63 Sulphoaluminate cement clinker 7 Light Burnt Magnesium Oxide 5 Submicron silica fume 10 Fly ash 9 Glass powder 6

[0049] In this embodiment, the low shrinkage and high air tightness concrete special cementitious material further includes 3wt% gypsum, 0.03wt% diethanol monoisopropanolamine and 0.1wt% pre-dispersed carbon nanotubes in terms of the total mass percentage of the raw materials in Table 1.

[0050] The special cementitious material of this embodiment is mixed into concrete, and the raw material ratio of each cubic meter of concrete is as follows: 686.6 kg / m 3 , polycarboxylate high efficiency water reducing agent 4kg / m 3 , sand 892.5kg / m 3 , stone 1090.8kg / m 3 , water 164.8kg / m 3 .

[0051] Example 2

[0052] As a preferred embodiment of the present invention, the specific composition of the low shrinkage and high airtightness concrete special cementitious material disclosed in this embodiment is shown in Table 2 below.

[0053] Table 2

[0054] raw material Mass percentage (wt%) Low heat Portland cement clinker 56 Sulphoaluminate cement clinker 14 Light Burnt Magnesium Oxide 3 Submicron silica fume 7 Fly ash 12 Glass powder 8

[0055] In this embodiment, the low shrinkage and high airtightness concrete special cementitious material further includes 3wt% gypsum, 0.03wt% diethanol monoisopropanolamine and 0.1wt% pre-dispersed carbon nanotubes in terms of the total mass percentage of the raw materials in Table 2.

[0056] The special cementitious material of this embodiment is mixed into concrete, and the raw material ratio of each cubic meter of concrete is as follows: 686.6 kg / m 3 , polycarboxylate high efficiency water reducing agent 4.1kg / m 3 , sand 892.5kg / m 3 , stone 1090.8kg / m 3 , water 164.8kg / m 3 .

[0057] Example 3

[0058] As a preferred embodiment of the present invention, the specific composition of the low shrinkage and high airtightness concrete special cementitious material disclosed in this embodiment is shown in Table 3 below.

[0059] Table 3

[0060] raw material Mass percentage (wt%) Low heat Portland cement clinker 54 Sulphoaluminate cement clinker 6 Light Burnt Magnesium Oxide 5 Submicron silica fume 10 Fly ash 15 Glass powder 10

[0061] In this embodiment, the low shrinkage and high airtightness concrete special cementitious material further includes 2wt% gypsum, 0.03wt% diethanol monoisopropanolamine and 0.1wt% pre-dispersed carbon nanotubes in terms of the total mass percentage of the raw materials in Table 3.

[0062] The special cementitious material of this embodiment is mixed into concrete, and the raw material ratio of each cubic meter of concrete is as follows: 686.6 kg / m 3 , polycarboxylate high efficiency water reducing agent 3.8kg / m 3 , sand 892.5kg / m 3 , stone 1090.8kg / m 3 , water 164.8kg / m 3 .

[0063] Example 4

[0064] As a preferred embodiment of the present invention, the specific composition of the low-shrinkage and high-airtightness concrete special cementitious material disclosed in this embodiment is shown in Table 4 below.

[0065] Table 4

[0066] raw material Mass percentage (wt%) Low heat Portland cement clinker 48 Sulphoaluminate cement clinker 12 Light Burnt Magnesium Oxide 3 Submicron silica fume 7 Fly ash 18 Glass powder 12

[0067] In this embodiment, the special cementitious material for low shrinkage and high airtightness concrete further includes 2wt% gypsum, 0.03wt% diethanol monoisopropanolamine and 0.1wt% pre-dispersed carbon nanotubes in terms of the total mass percentage of the raw materials in Table 4.

[0068] The special cementitious material of this embodiment is mixed into concrete, and the raw material ratio of each cubic meter of concrete is as follows: 686.6 kg / m 3 , polycarboxylate high efficiency water reducing agent 3.9kg / m 3 , sand 892.5kg / m 3 , stone 1090.8kg / m 3 , water 164.8kg / m 3 .

[0069] Comparative Example 1

[0070] The specific composition of the cementitious material of this comparative example is shown in Table 5 below.

[0071] Table 5

[0072] raw material Mass percentage (wt%) Ordinary Portland Cement (PO42.5) 70 Fly ash 20 Silica Fume 10

[0073] The cementitious material of this comparative example is mixed into concrete, and the raw material ratio of each cubic meter of concrete is as follows: Special cementitious material 686.6kg / m 3 , polycarboxylate high efficiency water reducing agent 3.7kg / m 3 , sand 892.5kg / m 3 , stone 1090.8kg / m 3 , water 164.8kg / m 3 .

[0074] Comparative Example 2

[0075] The cementitious material of this comparative example is the same as that of Example 1 except that low-heat silicate cement clinker is used to replace sulphoaluminate cement clinker and light-burned magnesia.

[0076] The cementitious material of this comparative example is mixed into concrete, and the raw material ratio of each cubic meter of concrete is as follows: Special cementitious material 686.6kg / m 3 , polycarboxylate high efficiency water reducing agent 3.9kg / m 3 , sand 892.5kg / m 3 , stone 1090.8kg / m 3 , water 164.8kg / m 3 .

[0077] Comparative Example 3

[0078] The cementitious material of this comparative example is the same as that of Example 1 except that low-heat silicate cement clinker is used to replace submicron silica fume and pre-dispersed carbon nanotubes are not added.

[0079] The cementitious material of this comparative example is mixed into concrete, and the raw material ratio of each cubic meter of concrete is as follows: Special cementitious material 686.6kg / m 3 , polycarboxylate high efficiency water reducing agent 4kg / m 3 , sand 892.5kg / m 3 , stone 1090.8kg / m 3 , water 164.8kg / m 3 .

[0080] Comparative Example 4

[0081] The cementitious material of this comparative example is the same as that of Example 1 except that low-heat silicate cement clinker is used instead of fly ash and glass powder.

[0082] The cementitious material of this comparative example is mixed into concrete, and the raw material ratio of each cubic meter of concrete is as follows: Special cementitious material 686.6kg / m 3 , polycarboxylate high efficiency water reducing agent 4.2kg / m 3 , sand 892.5kg / m 3 , stone 1090.8kg / m 3 , water 164.8kg / m 3 .

[0083] Comparative Example 5

[0084] The gelling material of this comparative example is the same as that of Example 1 except that diethanol monoisopropanolamine is not added.

[0085] The cementitious material of this comparative example is mixed into concrete, and the raw material ratio of each cubic meter of concrete is as follows: Special cementitious material 686.6kg / m 3 , polycarboxylate high efficiency water reducing agent 4kg / m 3 , sand 892.5kg / m 3 , stone 1090.8kg / m 3 , water 164.8kg / m 3 .

[0086] Comparative Example 6

[0087] The gelling material of this comparative example is the same as that of Example 1 except that carbon nanotubes are used to replace the pre-dispersed carbon nanotubes.

[0088] The cementitious material of this comparative example is mixed into concrete, and the raw material ratio of each cubic meter of concrete is as follows: Special cementitious material 686.6kg / m 3 , polycarboxylate high efficiency water reducing agent 4kg / m3 , sand 892.5kg / m 3 , stone 1090.8kg / m 3 , water 164.8kg / m 3 .

[0089] Comparative Example 7

[0090] The cementitious material of this comparative example is the same as that of Example 1, except that the pre-dispersed carbon nanotubes are not dispersed in the low-heat Portland cement clinker particles but are directly mixed with the raw materials.

[0091] The cementitious material of this comparative example is mixed into concrete, and the raw material ratio of each cubic meter of concrete is as follows: Special cementitious material 686.6kg / m 3 , polycarboxylate high efficiency water reducing agent 4kg / m 3 , sand 892.5kg / m 3 , stone 1090.8kg / m 3 , water 164.8kg / m 3 .

[0092] Test Case

[0093] (1) Testing the physical properties of cementitious materials

[0094] With reference to GB17671-1999 "Test method for strength of cement mortar (ISO method)" and GB / T1346-2011 "Test method for water consumption, setting time and stability of cement standard consistency", the physical properties of the cementitious materials of each embodiment and comparative example were tested, and the test results are shown in Table 6 below.

[0095] Table 6

[0096]

[0097] From the data in Table 6, it can be seen that by comparing Examples 1-4 and Comparative Example 1, it can be obtained that the special cementitious material, which is mainly composed of low-heat silicate cement clinker and obtained by modification and addition of pre-dispersed carbon nanotubes, has a compressive strength at each age that is increased by about 2-6 MPa compared with the conventional cementitious material ratio.

[0098] By comparing Example 1 with Comparative Examples 2-7, it can be obtained that the addition of sulfate cement clinker and light-burned magnesia can effectively improve the strength of concrete while alleviating the shrinkage of the system, especially the early strength; the addition of silica fume and pre-dispersed carbon nanotubes can effectively fill the pores inside the matrix, greatly improving its mechanical properties; the addition of DEIPA can promote the formation of hydration products under the synergistic effect of the gypsum component, optimize the pore size distribution, effectively improve the early mechanical properties of the matrix, and make the microstructure more compact; compared with directly adding carbon nanotubes into the matrix or not preparing clinker-CNT dry powder, the treatment method of carbon nanotubes by the special cementitious material of the present invention can effectively reduce the degree of entanglement between carbon nanotubes, make their network structure loose, and evenly fill them into the microporous structure, playing a good bridging and filling role, thereby improving the strength of the matrix.

[0099] (2) The concrete prepared in each embodiment and comparative example 1 was molded. The preparation method was as follows: weighed cementitious materials were poured into a mixer and mixed evenly, and then weighed sand and stone were added and stirred continuously to obtain a mixed dry material; a water reducer was mixed into water, and the water reducer was fully dissolved and mixed, and then poured into the mixed dry material to obtain a mixture, which was poured into a mold and allowed to stand for molding to obtain concrete, and the physical properties of the concrete were tested according to the following standards:

[0100] ① Compressive strength test: Refer to GB / T50081-2019 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete" to conduct compressive strength test on concrete specimens after standard curing for 28 days.

[0101] ② Gas permeability test: refer to JC / T2758-2023 "Test method for gas permeability of concrete" to treat the concrete specimens after standard curing for 28 days, and then carry out gas permeability test. Use cylindrical concrete specimens with a diameter of 150mm and a height of 50mm, and the test gas circuit pressure is 0.9MPa.

[0102] ③ Shrinkage test: Refer to the contact method in GB / T50082-2009 "Test method for long-term performance and durability of ordinary concrete" to test the drying shrinkage value of concrete on the 7th day.

[0103] The test results are shown in Table 7 below.

[0104] Table 7

[0105]

[0106] From the data in Table 7, it can be concluded that the airtight concrete prepared by the special cementitious material of the present invention through the closest packing theory and volume method has a greatly improved strength compared with the conventional concrete of the same grade in Example 1, and the 28d strength can be increased by about 20%, and the gas permeability coefficient is greatly reduced, and the gas permeability coefficient is 0.005-0.016×10 -18 m 2 It has excellent airtightness and its shrinkage rate is much lower than conventional concrete.

[0107] At the same time, by comparing Example 1 with Comparative Examples 2 to 7, it can be obtained that based on the low-heat silicate cement clinker system, the use of modified components (sulfoaluminate cement clinker, light-burned magnesium oxide and DEIPA), submicron materials and pre-dispersed carbon nanotubes can improve the internal pore structure of concrete to varying degrees, reduce the volume shrinkage of concrete, and improve the air tightness and durability of concrete. In addition, the combination of fly ash and glass powder can significantly optimize the workability and working stability of concrete, improve the dispersion stability of mineral admixtures and admixtures, and effectively improve the density of the concrete matrix. Compared with Comparative Examples 6 and 7, the carbon nanotubes that have been specially treated and uniformly dispersed in the clinker particles can achieve a tighter combination of carbon nanotubes and cementitious particles, thereby improving the overall stability and crack resistance of the material and improving the sealing performance of concrete.

[0108] Experimental data proves that the special cementitious material of the present invention is used to prepare airtight concrete, which can effectively improve the matrix density and crack resistance of concrete, has the advantages of good volume stability, high mechanical properties and airtightness, and can be suitable for application scenarios with changing service environments.

[0109] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.

Claims

1. A low shrinkage and high air tightness concrete special cementitious material, characterized in that: Includes the following raw materials in percentage by mass: The invention also comprises 2-3wt% of gypsum, 0.03wt% of diethanol monoisopropanolamine and 0.1wt% of pre-dispersed carbon nanotubes in terms of the total mass percentage of the above raw materials.

2. The low shrinkage and high air tightness concrete special cementitious material according to claim 1, characterized in that: The mineral composition of the low-heat Portland cement clinker includes: 29.9wt% C3S, 46.3wt% C2S, 1.8wt% C3A and 15.3wt% C4AF; the specific surface area of ​​the low-heat Portland cement clinker is 350-370m 2 / kg, 3d compressive strength ≥14MPa.

3. The low shrinkage and high air tightness concrete special cementitious material according to claim 1, characterized in that: The mineral composition of the sulphoaluminate cement clinker includes: 62.3wt% 27.5wt% C2S, 5.3wt% C4AF; the specific surface area of ​​the sulphoaluminate cement clinker is 390-420m 2 / kg, 3d compressive strength ≥40MPa.

4. The low shrinkage and high air tightness concrete special cementitious material according to claim 1, characterized in that: The light-burned magnesium oxide has a magnesium oxide content of ≥85wt%, an active magnesium oxide content of ≥65wt%, and a particle size of ≤40μm.

5. The low shrinkage and high air tightness concrete special cementitious material according to claim 1, characterized in that: The SiO2 content of the submicron silica ash is >93wt%, and the specific surface area is 23000m 2 / kg, 7d activity index ≥105%.

6. The low shrinkage and high air tightness concrete special cementitious material according to claim 1, characterized in that: The fly ash is Grade I fly ash with a specific surface area of ​​398m 2 / kg; the glass powder is waste quartz glass powder with a specific surface area of ​​450m 2 / kg.

7. The low shrinkage and high air tightness concrete cementitious material according to claim 1, characterized in that: The gypsum is natural gypsum or mixed gypsum, the anhydrite content in the natural gypsum or mixed gypsum is not more than 50wt% of the total gypsum, and the specific surface area of ​​the gypsum is 317-421m 2 / kg; the solid content of the diethanol monoisopropanolamine is ≥85wt%, and the pH value is 10.

24.

8. The low shrinkage and high air tightness concrete cementitious material according to claim 1, characterized in that: The pre-dispersed carbon nanotubes are obtained by pre-dispersing carbon nanotubes with a length of 100 to 200 μm and a diameter of 7 to 9 nm.

9. The low shrinkage and high air tightness concrete cementitious material according to claim 8, characterized in that: The preparation of the pre-dispersed carbon nanotubes is as follows: (1) weighing carbon nanotubes, polyvinyl pyrrolidone dispersant and deionized water in a mass ratio of 0.1:0.3:100 for later use; (2) adding the carbon nanotubes and polyvinyl pyrrolidone dispersant into deionized water, stirring, sealing and ultrasonically treating, and then high-pressure homogenizing to obtain a pre-dispersed liquid; (3) freeze-drying the pre-dispersed liquid to remove all water, and then placing it in a high-temperature drying oven to remove the polyvinyl pyrrolidone dispersant to obtain pre-dispersed carbon nanotubes; Preferably, the ultrasonic treatment in (2) is repeated 6 times, and each ultrasonic treatment lasts for 5 minutes; Preferably, the temperature of the high temperature drying oven (3) is 600° C., and the treatment time is 3 h.

10. The method for preparing a low shrinkage and high airtightness concrete special cementitious material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh low-heat silicate cement clinker, sulphoaluminate cement clinker, light-burned magnesia, submicron silica fume, fly ash and glass powder according to the mass percentage and set aside; weigh gypsum, diethanol monoisopropanolamine and pre-dispersed carbon nanotubes according to the percentage of the total mass of the above raw materials and set aside; S2, take out the reserved pre-dispersed carbon nanotubes, and weigh 10 times the mass of low-heat silicate cement clinker and 81.6 times the mass of isopropanol of the pre-dispersed carbon nanotubes, wherein the low-heat silicate cement clinker is weighed from the corresponding raw materials reserved in S1; divide the isopropanol into two parts, add the pre-dispersed carbon nanotubes to one part of the isopropanol, stir to dissolve and ultrasonically disperse to obtain a first mixture, then add the low-heat silicate cement clinker and the other part of the isopropanol to the first mixture, stir to dissolve and ultrasonically disperse to obtain a second mixture; place the second mixture in a high-temperature drying oven for treatment to remove the isopropanol, and obtain a clinker-CNT dry powder; Preferably, when the pre-dispersed carbon nanotubes are added to a portion of isopropanol, stirred to dissolve and ultrasonically dispersed, the ultrasonic time is 30 minutes; Preferably, when adding the low-heat Portland cement clinker and another portion of isopropanol to the first mixture, stirring to dissolve and ultrasonically dispersing, the ultrasonic time is 90 minutes; Preferably, the temperature of the high temperature drying oven is 100±5°C and the treatment time is 24h; S3, the sulphoaluminate cement clinker reserved in S1, light-burned magnesia, submicron silica fume, fly ash, glass powder, gypsum, diethanol monoisopropanolamine and the remaining low-heat silicate cement clinker, and the clinker-CNT dry powder obtained in S2 are mixed evenly to obtain the special cementitious material for low shrinkage and high airtightness concrete.

Citation Information

Patent Citations

  • Airtight concrete material and preparation method thereof

    CN110698137A

  • Airtight concrete and preparation method thereof

    CN114133190A

  • High-airtightness concrete and preparation method thereof

    CN114573288A

  • Low-heat corrosion-resistant Portland cement and preparation method thereof

    CN112479610A

  • Strong acid corrosion resistant cement mortar and preparation method thereof

    CN113754384A